2000
DOI: 10.1021/ie990699l
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Active Absorbent for Dry-Type Flue Gas Desulfurization from Calcium Oxide, Coal Fly Ash, and Gypsum

Abstract: As compared to a commercial absorbent prepared from Ca(OH) 2 , gypsum (CaSO 4 ) and coal fly ash, an absorbent prepared by use of CaO in place of Ca(OH) 2 , exhibited a higher activity for dry-type flue gas desulfurization . The order of the addition of the raw materials in the slaking procedure has much effect on the activity of the resulting absorbent. The activity of the absorbent increased further upon hydrothermal treatment following the kneading procedure. The period of hydrothermal treatment was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 21 publications
0
57
1
Order By: Relevance
“…In addition, SO2 and SO3 are harmful gases that contribute to formation of submicron acid particles that can penetrate human lungs and be absorbed into the bloodstream [144]. Many researchers have reported that blending FA with Ca(OH)2 or CaO can produce an adsorbent via a hydration process with a better SO2 reduction than that of hydrated lime [145][146][147]. Lee et al [148] found similar results, as shown in Figure 13.…”
Section: Sulfur Dioxidementioning
confidence: 84%
“…In addition, SO2 and SO3 are harmful gases that contribute to formation of submicron acid particles that can penetrate human lungs and be absorbed into the bloodstream [144]. Many researchers have reported that blending FA with Ca(OH)2 or CaO can produce an adsorbent via a hydration process with a better SO2 reduction than that of hydrated lime [145][146][147]. Lee et al [148] found similar results, as shown in Figure 13.…”
Section: Sulfur Dioxidementioning
confidence: 84%
“…For pressure hydration, absorbents with a BET specific surface area of 2.5-64.3 m 2 /g were obtained 5 . On the other hand, for steam hydration and water hydration, values of 24 m 2 /g 5 and 18-73 m 2 /g were obtained respectively 3,7 . It can be seen that the products of the pozzolanic reactions differs in each case depending on the methods of absorbent preparation as well as the fly ash composition and absorbents preparation parameters.…”
Section: Introductionmentioning
confidence: 96%
“…A wet-type FGD unit based on a limestone-gypsum method is most widely used and suitable for large-scale boilers such as those installed in coal or oil-fired power stations 3 . The wet-type FGD process has the advantage of using inexpensive limestone as a neutralizing agent, to produce commercial gypsum and to remove sulfur dioxides at high efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these processes is the dry-type desulfurization process operating at low temperature and which utilizes dry sorbent. The dry-type method for flue gas desulfurization (FGD) has recently attracted considerable research interest due to the drawbacks of wet-type methods [1,2].…”
Section: Introductionmentioning
confidence: 99%